Deep Lacerations—A Boon or Bane for Fracture Management: A Case Report. Issue 1 (December 2020) - Verma, Gaurav; Gothi, Bhavana; Tiwari, Arunesh Kumar; Agrawal, Amiya
In the modern era, the management of fractures is often done by open reduction and internal fixation. The open reduction essentially involves the use of incisions for the exposure of fractured segments followed by reduction and internal fixation. It is not uncommon to find deep lacerations in a trauma setting. These lacerations can be used to one's advantage (boon) for fracture management and can avoid the need for separate incisions. The purpose of this case report is to present the management of zygomatic complex fracture by utilizing deep lacerations.